Gastrointestinal Kaposi's sarcoma without cutaneous involvement - Inês de Almeida Mendes; Maria João Baptista (Sociedade Galega de Medicina Interna, 2022)
The incidence of Kaposi's sarcoma has been decreasing in the last years, but it remains the most common malignancy among patients with AIDS. The visceral involvement without cutaneous alterations is rare but has a worst prognosis, so it requires a high level of suspicion.